2000
DOI: 10.1116/1.1324644
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a 50 nm proximity x-ray lithography system and extension to 35 nm by resist material selection

Abstract: In this article, a 50 nm generation proximity x-ray lithography ͑PXRL͒ system is proposed using shorter wavelengths of exposure light down to around 3 Å. The illumination system uses a mirror at 1°incidence angle such as in the Canon stepper XRA-1000, which can be realized by coating with a fourth or fifth period metal such as Co or Rh. The resist containing chemical elements such as Cl, S, P, Si, and Br whose x-ray absorption edge lies in the wavelength band of the exposure light can yield a strong absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Kitayama et al 14 have proposed using a shorter wavelength, e.g., 0.4 -0.5 nm. The merits of this method are ͑1͒ good resolution at a larger gap, such as 50 nm resolution at a 10 m gap, ͑2͒ improvement of mask IP accuracy by using a thick diamond membrane, and ͑3͒ the higher sensitivity of the resist that is expected by incorporating Br, Cl or other elements.…”
Section: Extendibility For the Sub-100 Nm Nodementioning
confidence: 99%
“…Kitayama et al 14 have proposed using a shorter wavelength, e.g., 0.4 -0.5 nm. The merits of this method are ͑1͒ good resolution at a larger gap, such as 50 nm resolution at a 10 m gap, ͑2͒ improvement of mask IP accuracy by using a thick diamond membrane, and ͑3͒ the higher sensitivity of the resist that is expected by incorporating Br, Cl or other elements.…”
Section: Extendibility For the Sub-100 Nm Nodementioning
confidence: 99%
“…Furthermore, there is no practical tool for making fine pattern for nanotechnology besides electron beam direct writing, whose throughput is insufficient even for medium and small volume production. From these standpoints, second generation PXL ͑PXL-II͒ was proposed in 1999, 6 where it was shown that both resolution and throughput ͑resist sensitivity͒ were improved only by the selection of mirror, mask membrane, and resist materials. In PXL-II, the spectrum absorbed in the resist becomes harder and more narrowband, and the amount of absorption is remarkably increased owing to the materials selection.…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed and studied an advanced PXL technology, 11,12) called PXL-II, since 1999. The goals of PXL-II are to enhance the resolution to 50 nm and below, and to improve throughput by several times by modifying the mirror coating, mask substrate and resist materials of the conventional PXL.…”
Section: Introductionmentioning
confidence: 99%
“…In the PXL-II, the resist materials include special elements such as Cl, S, P, Si, and Br which have an absorption edge within the exposure spectrum. These elements in the resists are effective for achieving a high sensitivity 11) and suppressing the influence of the secondary electrons emitted from the Si substrate. 13) Furthermore, the resolution is resultantly improved, and the spectra absorbed in the resists containing these elements become narrowband as compared with those in the conventional resists consisting of the elements of C, H and O.…”
Section: Introductionmentioning
confidence: 99%